Cost-effectiveness analysis of personalised versus standard dosimetry for selective internal radiation therapy with TheraSphere in patients with hepatocellular carcinoma - Rognoni, Carla; Barcellona, Maria Rosa; Bargellini, Irene; Bavetta, Maria Grazia; Bellò, Marilena; Brunetto, Maurizia; Carucci, Patrizia; Cioni, Roberto; Crocetti, Laura; D’Amato, Fabio; D’Amico, Mario; Deagostini, Simona; et al. (Frontiers in Oncology, 2022)
Aims: To perform a Cost-Effectiveness Analysis (CEA) comparing personalised dosimetry with standard dosimetry in the context of selective internal radiation therapy (SIRT) with TheraSphere for the management of adult patients with locally advanced hepatocellular carcinoma (HCC) from the Italian Healthcare Service perspective. Materials & Methods: A partition survival model was developed to project costs and the quality-adjusted life years (QALYs) over a lifetime horizon. Clinical inputs were retrieved from a published randomised controlled trial. Health resource utilization inputs were extracted from administering questionnaires to clinicians in three oncology centres in Italy, respectively. Cost parameters were based on Italian official tariffs. Results: Over a lifetime horizon, the model estimated the average QALYs of 1.292 and 0.578 respectively for patients undergoing personalised and standard dosimetry approaches. The estimated mean costs per patient were 23,487 € and 19,877 €, respectively. The incremental cost-utility ratio (ICUR) of personalised vs. standard dosimetry approaches was 5,056 €/QALY. Conclusions: Personalised dosimetry may be considered a cost-effective option compared to standard dosimetry for patients undergoing SIRT for HCC in Italy. These findings provide evidence for clinicians and payers on the value of personalised dosimetry as a treatment option for patients with HCC.